Genes encoding receptors for insulin and insulin-like growth factor I are expressed in Xenopus oocytes and embryos. - Scavo, L (1991)
Insulin and insulin-like growth factor I (IGF-I) initiate their metabolic, growth, and differentiation effects through binding to the insulin receptor and the IGF-I receptor, two members of the tyrosine kinase family of receptors. To study the role of these peptides and receptors in early development, we used the polymerase chain reaction and embryo-derived RNA to generate partial cDNA sequences of the insulin receptor and IGF-I receptor from the amphibian Xenopus laevis. Three unique tyrosine kinase-related sequences were obtained. Two of the nucleotide sequences, XTK 1a and XTK 1b, corresponded to peptide that share 92% amino acid identity, and each is 89% identical to the human insulin receptor. The third sequence, XTK 2, corresponds to a peptide that has 92% amino acid identity with the human IGF-I receptor but only 80% identity with XTK 1a and XTK 1b. On the basis of these similarities, the pattern of conserved amino acids, and the tetraploid nature of the Xenopus genome, we suggest that XTK 1a and XTK 1b most likely represent the product of two different nonallelic insulin receptor genes, while XTK 2 may be one of the probable two Xenopus IGF-I receptor genes. By reverse transcription-polymerase chain reaction and gene-specific hybridization, expression of the three XTK sequences was detected in the oocyte, unfertilized egg, and embryos through gastrulation, neurulation, and tailbud stages. Competition binding assays with Xenopus membrane preparations demonstrated insulin receptors and IGF-I receptors in older tadpoles. IGF-I receptors were also present in oocytes, eggs, and gastrula embryos. By contrast, insulin binding was present but atypical in oocytes and was barely detected in eggs and gastrula embryos. The expression of receptors for insulin and IGF-I in early Xenopus embryos and their apparent distinct developmental regulation suggest that these molecules and their ligands may be important in early Xenopus development.